The short-run dynamics of inflation: estimating a "hybrid new Keynesian Phillips curve" for Argentina - D'Amato, Laura (2004)
Based on recent developments in the empirical modeling of the short-run dynamics of inflation, we estimate a "Hybrid New Keynesian Phillips Curve" for Argentina over the period 1993-2003, which assumes that while a fraction of the firms are forward-looking, the others use a backward-looking rule to set prices. We extend the model to a small open economy, considering the influence of nominal devaluation and foreign inflation on domestic prices. Although we find a significant forward-looking behavior, backwardness seems to be more relevant for domestic prices setting. Finally, we cannot reject verticality of the Phillips Curve in the long run.